Tinjauan Fiqih Muamalah terhadap Sistem Escrow dalam Marketplace - Dewi Nur Fatmah; Apriantini Kusumawati; Arin Tontami; Zainal Arifin (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
The development of marketplaces in digital commerce has created various problems, such as fraud, product discrepancies, and transaction disputes. To address these issues, marketplaces implement an escrow system as a transaction security mechanism by holding payment funds until the buyer confirms receipt of the goods. This study aims to analyze the escrow system from the perspective of fiqh muamalah using a normative legal research method through library research. The results show that the escrow system is generally permissible in Islam because it contains elements of wakalah, wadiah, and ujrah contracts and aims to ensure transaction security and protect the rights of all parties involved. However, its implementation must be conducted transparently and fairly to avoid elements of riba, gharar, and fraud (tadlis).